Design, synthesis and biological evaluation of cajanonic acid A analogues as potent PPAR γ antagonists. (15th January 2023) - Xu, Xiao-Ting; Shi, Li-Ying; Ban, Yu-Juan; Luo, Bi-Lan; Zhu, Gao-Feng; Guo, Bing; Tang, Lei; Sang, Zhi-Pei; Wang, Jian-Ta
Graphical abstract: Abstract: Peroxisome proliferator-activated receptor γ (PPAR γ) antagonists are a key instrument of insulin sensitizers since they have the ability to sensitize insulin and can avoid adverse reactions caused by receptor agonist. In this paper, two series of 28 novel Cajanonic acid A (CAA ) derivatives were designed and synthesized. The biological activity showed that a novel CAA derivative 9f was identified as a potential PPAR γ antagonist by medicinal chemistry efforts. The results in vitro displayed that compound 9f could improve the PPAR γ antagonist activity (96.2 % / 50.2 % decrease in PPAR γ transactivation at 10 μM / 1 μM, respectively). It also could improve the glucose consumption activity of insulin-resistant HepG2/3T3-L1 cell line (33.27 % / 72.61 % increase in glucose consumption). And in 3 T3-L1 adipocytes, it showed anti-adipogenesis activity (7.04 % increase in oil red staining). Further, in vivo study suggested that compound 9f could improve the oral glucose tolerance in db/db mice. Taken together, derivative 9f served as a promising candidate for anti-diabetic drug discovery and deserve further study.